Effect of the aerobic power test performed at low-medium altitude on the myostatin, pgc-1 alpha and klotho levels - Dündar, S. T.; Kuzucu, M.; Varol, S.R. (Gazzetta Medica Italiana - Archivio per le Scienze Mediche, 2023)
BACKGROUND: The aim of this study was to investigate the influence of the aerobic power test on myostatin, PGC-1, and Klotho levels in athletes who had acclimatized to the altitude.